2015
DOI: 10.46538/hlj.12.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Learning Outcomes of L2-Heritage Learner Interaction: The Proof is in the Posttests

Abstract: Over the last two decades, increasingly numbers of heritage language (HL) learners have been enrolling in the same classes as second language (L2) learners, given that most universities do not offer separate courses for HL learners (Beaudrie, 2012). This trend raises the question of whether L2 and HL learners benefit from working together. However, research on the interaction in L2-HL dyads has been scarce, and learning outcomes of L2-HL interaction have never been documented. This study examines whether L2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…According to Dewaele and Alfawzan (2018), when seeking to bridge the gap and distance between one's existing L2 skills and prospective L2 learning objectives, the ideal L2 self serves as a powerful motivation. In recent years, a slew of studies has been done to shed light on the link between the ideal L2 self and FLE (e.g., Ghasemi, 2018;Gupta & Gueneau, 2021;Henshaw, 2015).…”
Section: Ideal L2 Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Dewaele and Alfawzan (2018), when seeking to bridge the gap and distance between one's existing L2 skills and prospective L2 learning objectives, the ideal L2 self serves as a powerful motivation. In recent years, a slew of studies has been done to shed light on the link between the ideal L2 self and FLE (e.g., Ghasemi, 2018;Gupta & Gueneau, 2021;Henshaw, 2015).…”
Section: Ideal L2 Selfmentioning
confidence: 99%
“…According to some studies with a more comprehensive view of negative and positive classroom feelings, apprehension impedes learners' cognitive processing, while positive emotions contribute to widening their cognitive abilities (Matsuda & Gobel, 2001). Foreign language classroom apprehension (FLCA) and foreign language learning (FLE) have been identified as two important variables in predicting L2 outcomes (Henshaw, 2015). Several EFL researchers have expressed an interest in studying the impact of FLCA and FLE on general English courses (Matsuda & Gobel, 2001), learners' performance (Li, 2021), and gender (Ra & Rhee, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not LREs are correctly resolved can depend on several factors such as L2 learners' proficiency levels (e.g., Kim & McDonough, 2008), task type (e.g., Abadikhah, 2011), task mode (e.g., Niu, 2009) and even type of dyadic interaction (e.g., Storch, 2002). Critically, some evidence exists that L2 learners' involvement with LREs during peer interaction can lead to language development (e.g., Fernández Dobao, 2016;Henshaw, 2015;Kim, 2008).…”
Section: Language Related Episodes and Levels Of Engagementmentioning
confidence: 99%
“…Indeed, research has shown that HL learners tend to perform better on oral, rather than written, tasks, whereas the opposite is true for L2 learners (Bowles 2011b;Montrul 2013;Montrul et al 2008). Thus, L2 learners tend to have a stronger command of spelling conventions, which HL learners acknowledge as one of their weaknesses in terms of language skills (Colombi 1997;Henshaw 2015).…”
Section: Characteristics Of Heritage Language Learnersmentioning
confidence: 99%
“…Given these similarities and differences between L2 and HL learners, along with the fact that both types of learners are often enrolled in the same language courses, a growing body of research has started to examine the characteristics and the outcomes of L2-HL dyadic interaction (Blake and Zyzik 2003;Bowles 2011a;Bowles et al 2014;Fernández-Dobao 2020;Henshaw 2015;Torres and Cung 2019;Walls 2018). The first researchers to investigate L2-HL interactions, Blake and Zyzik (2003), examined text-based synchronous computer-mediated communication exchanges between 11 pairs of L2 and HL learners and it was found that in 75% of the episodes of negotiation, the HL learner aided the L2 learner, and out of a total of 30 episodes, 24 involved the selection of vocabulary.…”
Section: Research On L2-hl Interactionmentioning
confidence: 99%